Receivables portfolio of Polish companies - Bekas, Monika (Portfel należności polskich przedsiębiorstw, 2011)
Strong organizations have a decisive influence on the economic condition of a particular country. The lack of funds in due time leads to loosing financial liquidity and bankruptcy of enterprises. In order to define the situation of the receivables portfolio of Polish companies, research using Companies’ Receivables Index was applied. Its value is the highest since 2009. It means shortening the average waiting period for funds from the obtained trade credit. The proportion of companies declaring difficulties in the prompt covering of own liabilities which arose due to the lack of payments from customers is also decreasing. The costs of managing the portfolio of overdue receivables is going down. This rate also indicates the positive impressions of companies related to the quality of managing overdue receivables in the last three months
Ekonomia = Economics, 2011, Nr 2 (14), s. 178-184
Keywords: receivables; debt; bankruptcy; insolvency